Metastatic Vulvar Squamous Cell Carcinoma in a Mare - Santos, Ezequiel Davi dos; Leite Dau, Stefano; Policarpo Machado, Tanise; Setim, Diorges Henrique; Porto Alves, Leonardo; da Silva Leite, Juliana; Reis Ferreira , Ana Maria; Costa da Motta, Adriana (Acta Scientiae Veterinariae, 2022)
Background: Squamous cell carcinoma (SCC) is a common cutaneous neoplasm in horses, which mainly affects the external genitalia, oral cavity, and periocular region. The development of SCC metastases is rare in these animals, and the most common occurrence is a marked local infiltration. Exposure to ultraviolet rays and skin depigmentation are the main etiological factors of SCC. Definitive diagnosis of the neoplasm is performed through histological examination of lesions. The present report describes the clinical, anatomopathological, and immunohistochemical (IHC) aspects of a case of metastatic SCC, with the vulva as the primary site in a mare. Case: A 17-year-old mare, mixed breed, was referred to the Veterinary Hospital of the Universidade de Passo Fundo (UPF), with history of areas of depigmented skin (pinto coat), and clinical history of anorexia, frequent episodes of colic, and recumbency. During clinical evaluation, heart rate (68 bpm), rectal temperature (38.4ºC), and respiratory rate (48 mpm) were elevated, and the oral mucosa was pale. The mare also had an ulcerated tumor mass involving the vulva, which extended to the inguinal region and involved the mammary gland. A cytological aspirate of the vulvar tumor was performed, in which no neoplastic cells were found. Next, a biopsy of 2 distinct areas of the vulva was performed. The material was sent for anatomopathological examination, which showed markedly pleomorphic malignant squamous cells, with individual keratinization and high mitotic index, organized in trabeculae with rare keratin pearl-like formations. The exam allowed the diagnosis of SCC Grade II. Due to the poor prognosis and high cost of treatment, the owner consented to euthanasia and necropsy examination. During necropsy, the vulvar tumor mass was grayish, firm to hard, infiltrative, and had friable areas. Tumor foci suggestive of metastasis were also observed in inguinal, mesenteric, mediastinal and renal lymph nodes, adrenal glands, lung, pericardium, medullary canal, intercostal muscles, right 15th rib, and tissue surrounding the azygos vein. Samples from all organs were collected for anatomopathological examination. Diagnosis of metastatic vulvar SCC was confirmed through histological and IHC studies, which evaluated the expression of cytokeratins (AE1/AE3), as well as the proliferative activity of neoplastic cells through the PCNA marker. Discussion: The diagnosis of metastatic SCC was obtained through the observed clinical, necroscopic, histological, and IHC characteristics. This neoplasm usually appears in depigmented regions exposed to ultraviolet light, and older animals are more likely to be affected. The mare in the present case had areas of depigmented skin (pinto coat). The animal was kept in a paddock outdoor and exposed to constant solar radiation. Although rare in horses, manifestation of anorexia, progressive weight loss, and frequent colic episodes and recumbency may be closely related to the multiple sites of metastasis in the present case. The main histological findings of the neoplasm were the dense proliferation of malignant squamous cells with individual keratinization, arranged in a trabecular pattern and with rare formations of keratin pearls, in line with previous studies. During IHC evaluation, the neoplastic cells showed expression of cytokeratins (AE1/AE3), as well as high proliferative activity evidenced by the PCNA marker. Given this background, the present report describes the clinical, anatomopathological, and IHC aspects of a case of metastatic SCC with a primary site in the vulva of a mare. Keywords: equine, genital neoplasm, tumor embolism, squamous cell carcinoma, metastasis, immunohistochemistry.